Psikoedukasi “Remaja Berani, Tolak Sentuhan Tidak Pantas” Sebagai Upaya Preventif Pelecehan Seksual di SMA Negeri 9 Bulukumba - Irmayanti Irmayanti; Khalisah Humairah; Salsabila Rahman; Irdianti Irdianti (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2025)
The psychoeducation activity was conducted at UPT SMAN 9 Bulukumba with the aim of increasing adolescents’ understanding of sexual violence, especially related to inappropriate touching. The main objective was to serve as a preventive measure so that teenagers could protect themselves early on. The psychoeducation program titled "Brave Teens: Reject Inappropriate Touch!" was designed to enable adolescents to recognize, refuse, and confidently report socially and legally inappropriate actions. The methods used included administering pre-tests and post-tests to measure knowledge changes, delivering material on inappropriate touching, types of sexual violence, and how to refuse and report such incidents. The activities also involved discussions and Q&A sessions to deepen understanding and provide space for sharing experiences and opinions. A total of 30 female students participated in the program. The psychoeducation was carried out in stages, starting from preparation, material delivery, to final evaluation. Analysis results showed that after participating in the activity, participants’ understanding of the dangers of sexual violence increased significantly. Participants also became more confident in facing inappropriate situations. This psychoeducation activity proved effective in improving knowledge and shaping positive attitudes regarding the importance of self-protection against sexual violence. It is hoped that similar activities can create a safer school environment that is more aware of sexual violence issues and encourage adolescents to bravely say no and report if they experience or witness inappropriate behavior.Keywords: Psychoeducation; Adolescents; Sexual violence; Inappropriate touching.